Effects of postactivation potentiation on maximal vertical jump performance after a conditioning contraction in upper-body and lower-body muscle groups - Downey, R. J.; Deprez, D. A.; Chilibeck, P. D. (The Journal of Strength and Conditioning Research, 2022)
Postactivation potentiation (PAP) involves preperformance contractions that can condition a muscle to enhance subsequent force generation and power output. Our purpose was to examine the effects of conditioning contractions that are specific or nonspecific to the target performance on PAP. Resistance-trained subjects (14 males and 10 females) performed a 7-second isometric contraction involving back squat, bench press (as conditioning contractions), or a control condition (rest) on different days in random order, before maximal vertical jump performance. The back squat as a conditioning contraction increased maximal vertical jump by 1.1 ± 3.0 cm (p < 0.05); however, the bench press as a conditioning contraction unexpectedly reduced maximal vertical jump performance by 1.4 ± 2.7 cm (p < 0.05). Conditioning contractions used to elicit a PAP response should use muscles that are specific to the performance movement. Contractions that are not biomechanically similar to the performance movement may hinder subsequent performance.